Viet Nam: Foreign Direct Investment and Postcrisis Regional Integration - Vittorio Leproux; Douglas H. Brooks (Asian Development Bank (ADB), 2004)
Since Viet Nam started its transition from a centrally planned economy to a socialist-oriented market economy, many reforms have been implemented. The Foreign Investment Law signaled an important step toward Viet Nam's integration in the regional and international economic systems. The relatively low amount of foreign investment relative to other countries in East and Southeast Asia made more evident the necessity of a new set of reforms in order to compete with Asian neighbors, and principally with People's Republic of China, in the attraction of foreign direct investment. Even if foreign capital contributed in many important ways to the growth that Viet Nam has achieved since doi moi started, its impact in other areas was limited because of different problems affecting the Vietnamese economic system. This evidence underlines the need for reforms in the private sector, financial and banking sector, stateowned enterprises, and trade policy. Accession to the ASEAN Free Trade Area represents an important event and a new scenario where Viet Nam will compete and cooperate with its partners. It calls for a serious analysis of the changes occurring in comparative advantages of the Southeast Asian economies after the economic crises and of the role that Viet Nam can play in the regional production network.
hdl:11540/1913
Keywords: 330; Auslandsinvestition; Internationale Wirtschaftsbeziehungen; Regionale Wirtschaftsintegration; Vietnam